Танкер "Дербент": [повесть] / Юрий Крымов - Крымов Юрий Соломонович (Школьная библиотека, 1982)
Экземпляры: ф. 4 (20221101) / Инвентарный номер: 3197 / Цена: 0.50 / Авт.знак: К85 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6